Ablation of Atrial Fibrillation in Patients with Hypertension—An Analysis from the German Ablation Registry - Zylla, Maura M. (J Clin Med, 2020)
Background: Hypertension (HTN) constitutes a risk factor for the development of atrial fibrillation (AF), as well as for thromboembolic and bleeding events. We analysed the outcome after catheter ablation of AF in HTN in a cohort from the prospective multicenter German Ablation Registry. Methods: Between 03/2008 and 01/2010, 626 patients undergoing AF-ablation were analysed. Patients diagnosed with HTN (n = 386) were compared with patients without HTN (n = 240) with respect to baseline, procedural and long-term outcome parameters. Results: Patients with HTN were older and more often presented with persistent forms of AF and cardiac comorbidities. Major and moderate in-hospital complications were low. At long-term follow-up, major cardiovascular events were rare in both groups. Rates of AF-recurrence, freedom from antiarrhythmic medication and repeat ablation were not statistically different between groups. Most patients reported improvement of symptoms and satisfaction with the treatment. However, patients with HTN more frequently complained of dyspnea of New York Heart Association (NYHA) class ≥ II and angina. They were more often rehospitalized, particularly when persistent AF had been diagnosed. Conclusion: Catheter ablation of AF is associated with low complication rates and favorable arrhythmia-related results in patients with HTN. Residual clinical symptoms may be due to cardiac comorbidities and require additional attention in this important subgroup of AF-patients.